Pro SharePoint Migration Moving from MOSS 2007 to SharePoint Server 2010 - Malik, Sahil; Sistla, Srini; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Learn from Pro SharePoint Migration on how to migrate your existing farm - infrastructure, upgrade approaches, code, branding, and impact of new features of SharePoint 2010 - in a strategic way that results in smooth transition. Noted author Sahil Malik, with Srini Sistla, work together to provide detailed strategies and tools to assess, plan and execute a SharePoint 2010 migration that is efficient and cost-effective$1 (Band that doesn't use expensive third-party software. The "clean slate" approach embraced by this book, coupled with flexible tools designed by Microsoft and the author, will provide you with the statistics, charts, and diagrams necessary to perform a meaningful assessment of your current SharePoint 2007 environment. You'll then be able to plan the lowest-cost, least-hassle way to migrate your current environment, and its applications and data, to SharePoint 2010, and how to map your existing use of SharePoint 2007 to the new features and enhancements in SharePoint 2010. Pro SharePoint Migration will help you: Gain a better understanding of high level comparison and changes you need to learn between the two versions To migrate or not? Learn about new functionality that might replace your existing custom built code or non-code based solutions. Build a strong toolset to create, update, administer, and migrate 90% of the most commonly used SharePoint objects Grasp the intricacies of the SharePoint 2010 application programming interface (API) Become a better SharePoint 2010 administrator in your newly-migrated environments
Keywords: Computer science; Computer Science; Computer Science, general